PENGARUH GAYA HIDUP DAN BRAND IMPORT TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN BEKAS BRANDED (THRIFT) DALAM PRESPEKTIF MASLAHAH MURSALAH PADA MAHASISWA UNIVERSITAS NURUL JADID PAITON PROBOLINGGO - Himmah, Mufidatul; Munawaroh, Fadilatul (Penerbit Lafadz Jaya, 2025)
This study aims to examine the impact of lifestyle and foreign brands on the decision to purchase branded second-hand clothing (thrift) in Paiton District, Probolinggo Regency, focusing on students of Nurul Jadid University. The phenomenon of increasing consumption of branded second-hand clothing or thrift among students is not only caused by economic reasons, but also by lifestyle factors that are increasingly oriented towards sustainability and environmental awareness, as well as preferences for international brands that have prestige value. This study applies a quantitative descriptive method involving 100 students as respondents selected through a non-probability sampling technique with a purposive sampling method. Data collection was carried out by distributing questionnaires, and the collected data were then analyzed using the Statistical Package for Social Sciences (SPSS) version 22. 0. The findings of the study indicate that lifestyle and foreign brands have a significant positive influence on thrift purchasing decisions with an R2 value of 0.714, which means that 71.4% of the variation is influenced by these two variables, while the remaining 28.6% is influenced by other variables not examined in this study.